BIM deletion polymorphism predicts poor response to EGFR-TKIs in nonsmall cell lung cancer: An updated meta-analysis. Issue 10 (March 2019) - Su, Wenxia; Zhang, Xiaoyun; Cai, Xin; Peng, Meiyu; Wang, Fengbin; Wang, Yuliang
Abstract: Background: A germline deletion in BIM (B cell lymphoma-2-like 11) gene has been shown to impair the apoptotic response to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) in vitro but its impact on response to EGFR-TKIs in patients of nonsmall cell lung cancer (NSCLC) remains controversial. Methods: Eligible literature were searched and screened. Objective response rate (ORR) and disease control rate (DCR) were extracted and aggregated with odds ratio (OR). Hazard ratio (HR) and 95% confidence interval (CI) for progression-free survival (PFS) and overall survival (OS) were extracted and aggregated based on random-effect model. Results: Fourteen studies including 2694 NSCLC patients were eligible. Individuals harboring BIM deletion polymorphism had inferior ORR (OR = 0.49, 95% CI: 0.34–0.70, P  < .001), inferior DCR (OR = 0.50, 95% CI: 0.30–0.84, P  = .009). Patients with BIM deletion had shorter OS despite of the heterogeneity between countries (in subgroup of South Korea and Taiwan, HR = 1.34, 95% CI: 1.18–1.53, P  < .001; in subgroup of other countries, HR = 2.43, 95% CI: 2.03–2.91, P  < .001). The pooled analysis of PFS showed great heterogeneity ( I 2  = 79%). All the reported characteristics did not account for the heterogeneity. However, 2 subgroups could be obtained through sensitivity analysis. In one subgroup, patients with BIM deletion polymorphism had shorter PFS (HR = 2.03, 95% CI: 1.71–2.40, P < .001), while in the other subgroup, no significant difference was observed (HR = 0.92, 95% CI: 0.79–1.06, P  = .25). Conclusion: NSCLC patients with BIM deletion polymorphism show poor ORR, DCR, and OS after EGFR-TKIs treatment. BIM deletion polymorphism indicates poor response to EGFR-TKIs, and it could be used as a predictor to identify those who would benefit from EGFR-TKIs in NSCLC patients.